STRATEGI PEMASARAN DIGITAL UNTUK MENINGKATKAN PENJUALAN DI TOKO RAFIF CELL RAJABASA BANDAR LAMPUNG - Robbi Firman Saputra; Vonny Tiara (CV. Adiba Aisha Amira, 2026)
The purpose of this study is to find out the application of Toko Rafif Cell's digital marketing strategy in developing a business by promoting products that can increase its sales turnover as measured using a SWOT matrix and reviewing digital marketing strategies. This research was conducted using a descriptive qualitative approach with IFAS Matrix, EFAS Matrix, and SWOT Matrix methods to measure strengths, weaknesses, opportunities and threats. The data source is obtained from primary data and secondary data. Data collection techniques through observation, interviews and documentation. The results of this study show that the implementation of digital marketing strategies has been successfully implemented through social media so that there has been an increase in turnover and the implementation of digital marketing strategies. From the results of the IFAS matrix that is strong in identifying internal factors, the EFAS Matrix has responded well to existing opportunities and avoided threats coming from competitors.